Federal guidance on transportation equity shortcomings in practical application, case study: planning and implementation of Omaha Rapid Bus Transit (ORBT), Omaha, Nebraska - Groothuis, Jason (Kansas State University, 2023)
This report shows how polices and guidance for considering equity in public transit projects falls short in achieving its purpose of providing fair and equitable distribution of benefits and burdens. The recent planning and implementation of a bus rapid transit (BRT) route in Omaha, Nebraska is used as a case study. The Omaha Rapid Bus Transit (ORBT) route was used to replace route #2, a bus route with several more stop locations along an east to west transportation corridor (Dodge Street) in the eastern half of Omaha, Nebraska. To see how equity was considered in the planning and implementation phases, multiple analyses were performed using 2019 American Community Survey 5-Year Estimates (ACS) data, observed boarding and alighting counts, and the results of the most recent on-board survey which were all available during the planning and implementation phases of ORBT. By exclusively examining data available to planners during the planning process, it can be seen to what extent equity was likely considered and the likely distribution of benefits and burdens.
Keywords: Transportation planning; Equity; Environmental justice; Title VI; Bus rapid transit; Measuring accessibility to transit